Kinematic analysis of proximal-to-distal and simultaneous motion sequencing of straight punches - Fuchs, P. X.; Lindinger, S. J.; Schwameder, H. (Sports Biomechanics, 2018)
Consecutive proximal-to-distal sequencing of motion is considered to be integral for generating high velocity of distal segments in many sports. Simultaneous usage of proximal and distal segments as seen in martial arts is by far less well investigated. Therefore, the aim of the study was to characterise and differentiate the concepts of consecutive (CSM) and simultaneous (SSM) sequence of motion in straight reverse punches as practised in Practical Wing Chun. Four experienced martial artists succeeded an eligibility test for technical proficiency in both concepts and performed a total number of 20 straight punches per concept. Eight MX13 Vicon cameras (250 fps) and Visual3D were used for motion capture and analyses. Both motion concepts showed proximal-to-distal sequencing of maximal joint velocities but, in SSM, this was coupled with simultaneous initiation. Key characteristics were: high pelvis momentum and backswing of shoulder and elbow (CSM); and importance of shoulder involvement (SSM). Different ranges of motion, timing aspects and achieved maximal angular velocities distinguished both concepts, which led to differences (p < 0.05) in fist velocity at contact, execution time, distance and horizontal shift of the centre of mass. Proper application of both concepts depends on the environmental setting, situational requirements and individual fighting style.